Estudo da atividade citotóxica e do potencial antitumoral do extrato acetônico das sementes de Annona muricata L.(AMSA), em modelos experimentais in vitro e in vivo - Rios, Maria Erivanda França (2013)
Annona muricata, popularly known as soursop, is a plant widely used in folk medicine as teas and infusions for the treatment of various diseases such as cancer. The aim of this study was to cytotoxicity evaluate the antitumor activity of the acetone extract of the seeds of Annona muricata. This study was conducted with a panel of four tumor cell lines, HL-60 cells, HCT-116, SF-295 and OVCAR-8 IC50 values obtained 0.1944 µg/ ml, 0.1488 µg/mL, 0.0601 µg/mL and 0.0987 µg/mL, respectively. In the analysis across from erythrocytes of mice obtained the IC50 of 9.23 µg/mL. The acute toxicity study was conducted in vivo and DL50 was 310.2 mg/kg. The study of hemolytic activity was performed using cell suspension from mice without causing lysis. The evaluation study antitumor doses (7.5, 15 and 30mg/kg/day orally) in mice transplanted with Sarcoma 180 showed activity at all doses, causing a reduction of 48.41% of tumor growth at the highest dose . Analyses of liver and kidney revealed that there were some changes in the liver, such as steatosis and focal necrosis suggesting liver toxicity in mice treated with acetone extract of the seeds of Annona muricata. These changes are, however, considered the possible reversal of the tissue with treatment discontinuation or dose adjustment. Biochemical analysis revealed an increase in serum creatinine at doses of 15 and 30 mg/kg/day. In haematological tests there were no changes in the groups treated with acetone extract of the seeds of Annona muricata. The results showed little change in physical parameters of the animal, biochemical and hematological showing that the extract is well tolerated and less toxic.